Odpowiedź :
Odpowiedź:
7 i 1/2 -3 + 2*3/4 ( skracamy 2 i 4 przez 2)= 7 i 1/2 -3 + 3/2= 4 i 1/2 +1 i 1/2=6
2 i 1/2 *3 +4 *1 i 1/2= 5/2*3 + 4*3/2( skracamy 4 i 2 przez 2)= 15/2 + 6=
= 7 i 1/2 +6= 13 i 1/2
2 i 1/4 *2 +3 i 3/4= 9/4 *2 + 3 i 3/4 ( skracamy 4 i 2 przez 2)=
= 9/2 + 3 i 3/4= 4 i 1/2 + 3 i 3/4= 4 i 2/4 + 3 i 3/4= 7 i 5/4= 8 i 1/4
9- 1 i 3/5 *4= 9 - 8/5*4 = 9- 32/5= 8 i 5/5- 6 i 2/5 = 2 i 3/5
Szczegółowe wyjaśnienie:
Odpowiedź:
6
13 i 1/2
8 i 1/4
2 i 3/5
Szczegółowe wyjaśnienie:
Kolejność działań itp.